Development of protocol for in vitro rooting and hardening of doubled haploid line of Tagetes erecta L. derived through ovule culture - Mehraj, Uzma; Panwar, Sapna; Singh, Kanwar Pal; ., Namita; Pandey, Renu; Solanke, Amolkumar U.; Mallick, Niharika (Indian Journal of Horticulture, 2018)
In vitro regenerated doubled haploid line of Tagetes erecta L. (African marigold) derived through ovule culture using non axillary explants, were subjected to different rooting media wherein the elongated micro shoots were transferred individually to the rooting medium consisting of Half MS basal media supplemented with sucrose (60 g/l) and different concentrations of Auxins, IBA (0.5, 1.0 mg/l), NAA (0.5, 1.0 mg/l) and their combination IBA + NAA ( 0.25 mg/ l + 0.25 mg/l). The results revealed that treatment with ½ MS + IBA (0.5 mg/l) was best for parameters like number of days taken for root initiation (3.44 ), number of roots per shoot (33.54), per cent rooting (93.67). Although, the longest root length (9.64 cm) was found in treatment comprised of MS only and devoid of hormones (control) which produced roots that were light green in colour, thin, lanky and showed low performance while, roots produced in treatment with ½ MS supplemented with IBA (0.5 mg/l) medium were shortest of all treatments (3.43 cm) but were healthy, white and thick, vigorous and showed maximum survival. Thereafter, the rooted plants were transferred to the plastic pots containing different hardening media like soil, soilrite and mixture of cocopeat, vermiculite and perlite in the ratio of 1:1:1 (v/v) with ½ strength MS medium containing only macro and micro-salts. The results showed that the treatment comprising of cocopeat, vermiculite and perlite in the ratio of 1:1:1 (v/v) was best for parameters like per cent survival after 15 days (96.80), per cent survival after 30 days (95.00), per cent survival after 45 days 95.00, shoot length after 15 days (12.50 cm), shoot length after 30 days (15.46 cm), shoot length after 45 days (23.40 cm) and number of leaves per plant (18.60).